Perilaku Generasi Millenial dalam Pengambilan Keputusan Berinvestasi di Pasar Modal - Satria, R Adhi; Yuhertiana, Indrawati (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The Millennial Generation has a very fundamental role in the investment sector, where its existence is able to play a role in strengthening capital market stability in the new era. However, the financial behavior (behavior financial) of the millennial generation as individual investors in terms of overconfidence, financial knowledge (financial literacy) and herding behavior is considered influential in making investment decisions in the capital market. The population in this study is 2,076 investors in the Surabaya Beginner Stock Investor Community (ISP) in 2023. The sampling technique used a non-probability sampling approach with the slovin formula and obtained a total sample of 100 research samples. Data collection was carried out using a questionnaire distributed to the Surabaya Beginner Stock Investor Community (ISP). Hypothesis testing used the Patial Least Square (PLS) analysis tool, with Smart PLS Version 3 software. The results showed that there was a significant influence between overconfidence and financial literacy behavior on investment decision making, and it was found that there was no effect of herding behavior on investment decision making. These findings indicate that investors in the context of the beginner stock investor community in Surabaya tend to be more independent in making decisions and are not affected by collective actions that may be irrational. Keywords: overconfidence behavior, financial literacy, herding behavior, investment decisions.